Contextual Meaning Construction in Mens Rea A Setup PunchlineAnalysis of Pandji Pragiwaksono Stand-up Comedy - ERNI SETYOWATI; Sudar; Tusino (Gema Cendekia Institute, 2026)
Mens Rea is a Latin legal term that translates to “guilty mind”. It refers to defendant’s criminal intent, knowledge, or mental state at the time they commited a crime. Stand-up comedy is a style of comedic performed in person where the comedian speaks directly to the audience with humor, irony, or satirical observations step. Many comedians use their performances to criticize, express opinions and challenge audiences with material thatmakes them question current events instead of just entertaining. This research analyzes how the contextual meaning is constructed from Mens Rea, a stand-up comedy performance by Pandji Pragiwaksono. More specifically, it examines how the interplay of setup and punchline generates comical effects and informs the audience's understanding of the performance as a whole. Stand-up comedy relies not only on lexical meanings but also on contextual meanings. The audiences construct and reconstruct meanings according to the communication situation, sharedbackground knowledge, and sociocultural experience. This study uses a qualitative approach within pragmatic-semantic framework. The data consist of utterances extracted from the Mens Rea performance transcription. Procedures concerning to the data collection and organizations are such as; researchers watch, listen, and documented the utterances by typewriting. Analyzed using data reduction. Categorizing the utterance. Interpretation the data and concluded the results. The findings show four major strategies in building contextual meaning: (1) contextual reframing that shifts audience’s expectations, (2) sociocultural references relying on shared public knowledge, (3) lexical reinterpretation via analogy, ambiguity, and wordplay, (4) pragmatic incongruity that purposefully breaks the assumption established in the setup. These strategies allow for the reconstruction of ordinary political, social, and everyday experiences into humorous discourse while at the same time communicating criticism and social commentary.